Schur convexity properties of the weighted arithmetic integral mean and Chebyshev functional - Long Bo-Yong; Jiang Yue-Ping; Chu Yu-Ming (Journal of Numerical Analysis and Approximation Theory, 2013)
In this paper, we discuss the Schur convexity, Schur geometrical convexity and Schur harmonic convexity of the weighted arithmetic integral mean and Chebyshev functional. Several sufficient conditions, and necessary and sufficient conditions are established.